Somatostatin receptor radionuclide therapy in neuroendocrine tumors. Issue 3 (March 2021) - Haider, Mintallah; Das, Satya; Al-Toubah, Taymeyah; Pelle, Eleonora; El-Haddad, Ghassan; Strosberg, Jonathan
Abstract : Peptide receptor radionuclide therapy (PRRT) using 177 Lu-DOTATATE has been approved for the treatment of gastroenteropancreatic NETs. An understanding of benefits and risks is important for the appropriate implementation of this therapy. This review summarizes study data supporting the use of radiolabeled somatostatin analogs for the treatment of advanced NETs and highlights risks, including potential toxicities in specific populations. Key ongoing clinical trials, including randomized studies, are designed to better define the position of PRRT within the broader therapeutic landscape. Preclinical and early-phase human studies are focused on the development of novel somatostatin-receptor agonists and antagonists, new radionuclides, and radiosensitizing combination therapies.